Perilaku Kolektor Seni Indonesia Dalam Memilih Hic Et Nunc Sebagai Lokapasar NFT (Non-Fungible Token) - Hartini, Resti; Ratna, Vegasari Adya (Jurnal Paradigma, 2023)
Public interest in cryptocurrencies and NFTs has increased since the Covid-19 pandemic, especially for artists and art lovers. The function of NFTs is to apply the usability of credits or royalties to a work. Hic et Nunc is an alternative marketplace that is known to be environmentally friendly compared to other Ethereum-based marketplaces that are known for high gas fees and ecological issues. Unfortunately, in the midst of its popularity, Hic Et Nunc was discontinued without any warning and its website is no longer accessible. This situation created sites that mirrored Hic Et Nunc such as objkt.com or henext.xyz. This research discusses the factors that make art collectors have loyalty to Hic Et Nunc by staying and not switching to the dominant market location. The research method was based on a descriptive qualitative approach with in-depth interviews with 3 informants, all of whom are active art collectors and loyal to the Hic Et Nunc marketplace. Based on consumer behaviour theory and market theory, the results stated that collectors are influenced by their work, social and cultural environment. Besides, the factors for choosing Hic et Nunc as a marketplace include being an alternative platform to the dominance of Ethereum, a digital investment medium and recognition by the social environment.Keywords: NFTs, Hic et Nunc, Collectors, Marketplaces